PENGARUH JENIS ADSORBEN DAN LAMA PEMUCATAN TERHADAP KARAKTERISTIK MUTU MINYAK KEM1RI - M. P. LAKSMANAHARDJA; CHRISTINA WINARTI; DJAJENG SUMANGAT; B. SOFIANNA SEMBIRING (Pusat Penelitian dan Pengembangan Perkebunan, 1999)
Effect of adsorbent type and bleaching process time on the characteristics ofcandle nut oilResearch on bleaching of candle nut oil was conducted in Laboratory of Postharvest Technology, RISMC from November 1995 to March 1996. The crude candle nut oil has to be purified so that it can be used for many purposes and it can increase the storage peiode One of the stages in puification is bleaching The aims of study were lo find out the type and amount of adsorbent and the bleaching time The experiment used completely randomized design with factoial expeiment and two replications Treatments tested were types of adsorbent (A): activated charcoal, coconut shell charcoal and ash of paddy busk, amount of adsorbent with 1. 2. aid 3% oil weight; and bleaching time (B): 1. 2. and 3 hours. Result showed that type of adsorbent gave a significant effect on saponification vahie, acid value and FFA content; bleaching time affected on acid value and FFA content. There was no significant effect on iodine value in all of the treatments tested. The optimum treatment combina¬ tion was activated charcoal, with 1% concentration for one hour.